Peran Pendidik dalam Meningkatkan Minat Belajar di PAUD SKB Sidoarjo - Rahmawati, Gita Tri Yuni; Artha, I Ketut Atmaja Jhony (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This study aims to 1) examine the role of educators in increasing interest in learning in Early Childhood Education of Sidoarjo Learning Activity Center. 2) Assessing the supporting factors of educators in increasing interest in learning in Early Childhood Education of Sidoarjo Learning Activity Center. 3) Assessing the inhibiting factors of educators in increasing interest in learning in Early Childhood Education of Sidoarjo Learning Activity Center. The approach and type used in this research is descriptive qualitative, with the research location in Early Childhood Education of Sidoarjo Learning Activity Center. Data collection techniques through in-depth interviews, participatory observation, and documentation. This study uses data analysis by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that the role of educators as motivators in increasing interest in learning in Early Childhood Education of Sidoarjo Learning Activity Center is going well and it is proven that during learning students have feelings of joy, involvement, interest, and attention in children's learning.. Supporting factors include the health of students, qualified educators, learning environment conditions, rewards, and learning methods. The inhibiting factors include inadequate infrastructure and lack of cooperation from parents.